Evaluation of anti-sepsis activity by compounds with high affinity to lipid a from HuanglianJiedu decoction. (2nd November 2017) - Xu, Yubin; Guo, Song; Chen, Guirong; Zhang, Mingbo; Zhang, Xu; Dou, Deqiang
Abstract: Context: HuanglianJiedu decoction (HJD) is a classic prescription for heat-clearing away and detoxifying, which is used for the clinical treatment of sepsis, due to sepsis refers to the systemic inflammatory response induced by infection in western medicine, and infection belongs to the category of poison-heat syndrome in traditional Chinese medicine. Objectives: Previous study had elucidated the effective components from HJD with high affinity to lipid A, which can generate the release of pro-inflammatory-cytokines, resulting in sepsis. Now the anti-sepsis activities of these compounds were evaluated. Materials and methods: Immunofluorescence, immunohistochemical staining, ELISA and MTT methods were used to evaluated these compounds. Results: Immunofluorescence analysis evaluated the effects of compounds on the binding of FITC-LPS to RAW264.7 cells, and showed the fluorescence intensity was significant attenuated in geniposides, palmatine, baicalin and berberine groups (64 and 128 μg/mL) compared with model group ( p  < 0.05), which showed these compounds inhibit the combination of LPS with receptor of cells; immunohistochemical staining and ELISA method showed the TLR4 receptor expression, IL-6 and TNF-α levels were significant decreased in the groups treated with compounds, indicating that geniposides, baicalin, palmatine and berberine can play the role of anti-sepsis by inhibiting the expression of TLR4, the releasing of IL-6 and TNF-α; MTT assay showed that palmatine and berberine had a weak effect on cell viability, while others not, indicating that the compounds have protective activity. Discussion and conclusions: It could be concluded the high affinity binding between these compounds and lipid A may be an important basis for its anti-LPS activity in vitro .